Full‐thickness endotracheal tube defect resulting in an anaesthetic circuit leak. (10th March 2022) - Miller, Lucy; Lord, Samuel
Abstract: Background: Loss of endotracheal tube (ETT) integrity secondary to dental damage is reported in the human literature. Objective: To describe this problem in equine anaesthesia. Study design: Case report. Clinical summary: An 18‐year‐old Standardbred gelding presented out of hours with colic signs. Findings on clinical examination and pain refractory to analgesia meant that exploratory laparotomy was elected for. Prior to general anaesthesia (GA) leak testing of the anaesthetic machine was performed and the pilot balloon of the endotracheal tube (ETT) was inflated to confirm cuff integrity. Intermittent‐positive pressure ventilation (IPPV) was initiated immediately following placement in dorsal recumbency and connection to the anaesthetic machine. During the inspiratory phase of IPPV, a loud gas leak was audible from the oropharynx and minimal thoracic excursion was observed, with repeated inflations of the ETT cuff unsuccessful at abolishing the leak. Due to suspicion of a defect within the silicone ETT itself, a support arm was used to abolish the curvature of the ETT, maintaining it in a straighter plane. This intervention abolished the leak allowing effective IPPV. After completion of GA, a close inspection of the ETT revealed a full‐thickness laceration, thought to be a result of dental damage at an earlier date. Main limitations: A single case is described. Conclusions: This report emphasises the importance of thorough inspection of the ETT prior to use to effectively secure the airway and enable IPPV provision in critical cases. Zusammenfassung: Hintergrund: In der Humanmedizinischen Fachliteratur wird über den Verlust der Integrität des Endotrachealtubus (ETT) infolge von Zahnschäden berichtet. Ziel: Beschreibung des Problems in der Pferdeanästhesie. Studiendesign: Fallbericht. Klinische Zusammenfassung: Ein 18‐jähriger Traber‐Wallach wurde außerhalb der Arbeitszeit mit Koliksymptomatik vorgestellt. Aufgrund der klinischen Untersuchung und der Schmerzen, die auf Analgetika nicht ansprachen, wurde eine explorative Laparotomie durchgeführt. Vor der Vollnarkose (GA) wurde das Anästhesiegerät auf Dichtigkeit geprüft und der Pilotballon des Endotrachealtubus (ETT) aufgeblasen, um die Integrität der Manschette zu bestätigen. Die intermittierende Überdruckbeatmung (IPPV) wurde unmittelbar nach der Lagerung in Rückenlage und dem Anschluss an das Narkosegerät eingeleitet. Während der Inspirationsphase der IPPV war ein lautes Gasleck aus dem Oropharynx zu hören, und es wurde eine minimale Thoraxexkursion beobachtet, wobei das wiederholte Aufpumpen der ETT‐Manschette das Leck nicht beseitigen konnte. Da der Verdacht auf einen Defekt im ETT selbst bestand, wurde ein Stützarm verwendet, um die Krümmung des ETT zu beseitigen und ihn in einer geraderen Ebene zu halten. Durch diesen Eingriff wurde das Leck beseitigt und eine wirksame IPPV ermöglicht. Nach Beendigung der GA wurde bei der genauen Inspektion des ETT ein Riss in voller Ausdehnung festgestellt, der vermutlich auf eine frühere Zahnverletzung zurückzuführen war. Hauptlimitation: Beschreibung eines einzelnen Falles. Schlussfolgerungen: Dieser Bericht unterstreicht die Bedeutung einer gründlichen Inspektion des ETT vor der Anwendung, um den Atemweg effektiv zu sichern und die IPPV in kritischen Fällen zu ermöglichen.